2022
DOI: 10.1002/jsfa.12066
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tea polyphenol‐ozonated slurry ice treatment on the quality of large yellow croaker (Pseudosciaena crocea) during chilled storage

Abstract: BACKGROUND:The aim of the current study was to evaluate the synergistic effects of tea polyphenol-ozonated slurry ice on the quality, physicochemical and protein characteristics of large yellow croaker (Pseudosciaena crocea) during chilled (4 °C) storage. To 0.3% tea polyphenol combined with ozone water was added sodium chloride until the salt concentration reached 3.3% and with the use of an ice machine the mixture formed the tea polyphenol-ozonated slurry ice. Microbial [total viable count (TVC)], physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The present results showed that TBA increment in MPE samples was significantly lower over the storage period, which was 43.56% less than that of the control (818 ± 0.003 mg-malonaldehyde/kg) at the end of the storage period, which indicates that MPE could effectively retard lipid oxidation during frozen storage because of its high antioxidant activity. The result of this study is also supported by some previous studies, wherein it was reported that polyphenolic extracts from clove buds, thinned young apples, and grape seed extract showed strong antioxidant effects and significantly restrained increases of TBA in surimi. …”
Section: Results and Discussionsupporting
confidence: 89%
“…The present results showed that TBA increment in MPE samples was significantly lower over the storage period, which was 43.56% less than that of the control (818 ± 0.003 mg-malonaldehyde/kg) at the end of the storage period, which indicates that MPE could effectively retard lipid oxidation during frozen storage because of its high antioxidant activity. The result of this study is also supported by some previous studies, wherein it was reported that polyphenolic extracts from clove buds, thinned young apples, and grape seed extract showed strong antioxidant effects and significantly restrained increases of TBA in surimi. …”
Section: Results and Discussionsupporting
confidence: 89%
“…α‐helix and β‐sheet can manifest protein conformation, while its looseness degree can be demonstrated by a random coil and β‐turn (Lan et al ., 2022a). The fresh samples contained 28.37% β‐sheet, 15.18% random coil, 32.29% α‐helix, and 24.16% β‐turn.…”
Section: Resultsmentioning
confidence: 99%
“…The total ratio of α‐helices and β‐sheets (more organised secondary structures) in samples treated by ClO 2 , SAEW, and ClO 2 combined with SAEW (53.98–59.65%) was significantly increased at day 12 compared to that in CK group (46.10%). In addition, on the 12th day, samples in CK group formed a slightly loose conformation, which was caused by a larger proportion of random coils (22.11%) than those in other groups (15.24–21.57%) (Lan et al ., 2022a). At day 12, the total ratio of α‐helices and β‐sheets in ClO 2 + SAEW group was higher than that in ClO 2 or SAEW group, reaching 59.65%, with the lowest ratio of (15.24%), resulting in a more regular secondary structure.…”
Section: Resultsmentioning
confidence: 99%
“…The method for performing SDS–PAGE was based on a method reported previously 15 . The diluted MP solution (2 mg·mL ‐1 ) was mixed with a quarter of its volume of SDS‐PAGE sample loading buffer with or without β ‐mercaptoethanol ( β ‐ME).…”
Section: Methodsmentioning
confidence: 99%
“…The method for performing SDS-PAGE was based on a method reported previously. 15 The diluted MP solution (2 mg•mL -1 ) was mixed with a quarter of its volume of SDS-PAGE sample loading buffer with or without ⊎-mercaptoethanol (⊎-ME). After heating at 90 °C for 3 min, 10 μL samples were added to a 5% stacking gel and 12% separating gel.…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresismentioning
confidence: 99%